The Unconscious, Bodily, Feeling “I” (On the Issue of the Dissociative Process) - Mikayelyan, Vladimir (Bulletin of Yerevan University E: Philosophy, Psychology, 2018)
Some features of the dissociative syndrome, in which the corporality of personality is presented as the focus of analysis, are considered in the article. In particular, the problem of the inclusion of corporeality – the schemes and feelings of the body in a dissociative process, is analyzed. In addition, the question of whether the disease of the individual is due to its identity deserves more attention.